Has Globalization Really Increased Business Cycle Synchronization? - Monnet, Eric (IMF Working Papers; Working Paper ;, 2016)
This paper assesses the strength of business cycle synchronization between 1950 and 2014 in a sample of 21 countries using a new quarterly dataset based on IMF archival data. Contrary to the common wisdom, we find that the globalization period is not associated with more output synchronization at the global level. The world business cycle was as strong during Bretton Woods (1950-1971) than during the Globalization period (1984-2006). Although globalization did not affect the average level of co-movement, trade and financial integration strongly affect the way countries co-move with the rest of the world. We find that financial integration de-synchronizes national outputs from the world cycle, although the magnitude of this effect depends crucially on the type of shocks hitting the world economy. This de-synchronizing effect has offset the synchronizing impact of other forces, such as increased trade integration.